The role of recruitment marketing and employer branding in attracting Gen Z talent - Saari, Ronja; Koivunen, Ninni (2025)
One of the current changes in working life is the entry of Generation Z (people born between 1995–2012) into the workforce. This thesis explored how organizations implement recruitment marketing and employer branding strategies to attract Gen Z job seekers by examining how companies implement recruitment marketing and employer branding when the target group is Gen Z, how the employer branding is adapted to meet their expectations, and what role social media plays in this process.